教師參與海洋環境教育專業發展方案的投入程度：關注階層架構之運用 Teacher Engagement in Professional Development for Marine Environmental Education Implied by the Stages of Concern Framework - 李弘善 Hung-Shan Li; 劉湘瑤 Shiang-Yao Liu; 陳麗淑 Li-Shu Chen; 葉庭光 Ting-Kuang Yeh; 葉佳承 Chia-Cheng Yeh (National Taiwan Normal University, 2017)
海洋與環境教育已列為中、小學課程重大議題之一，以融入既有學科領域課程的方式進行教學，教師必須有能力選取適當素材、運用有效的教學法並選擇適當的時機在課室中實施，因此凸顯教師專業發展的需求。本研究規劃一個以建立海洋環境教育實務社群為目標的專業成長方案，分成招募期、媒合期和協作期等三階段。本研究報導此專業成長方案在招募階段對29位參與者所做的問卷調查結果，據以推估其持續參與專業成長方案和實施教學的意願。報名前施以問卷結果顯示，多數教師參與本研習課程的期望是充實海洋與環境議題的內容知識和蒐集可用的教學資源。運用關注階層問卷診斷教師對議題融入教學的關注類型，結果顯示僅七位參與者屬於有經驗的使用者，能關注此類教學對學生產生的影響和尋求合作管道，其中六位能積極投入專業成長方案；多數參與者仍屬於非使用者，處於覺察和資訊的關注階層，較低比例願意加入實務社群。本研究結果驗證理論模式，當參與者對革新課程的關注階層愈高，則持續參與專業發展的意願也愈高。建立實務社群作為專業成長方案的目標，可因應高關注階層的參與者對於尋找合作機會和提升學生學習成效的需求。 Marine environmental education is a crucial topic that should be addressed by elementary and secondary school curricula. Teachers are expected to be capable of implementing marine education by adopting appropriate materials and effective teaching strategies. Consequently, there is an increasing need for teachers' professional development to consider this educational field. A community of practice (CoP) professional development program was designed in this study to meet this need. The program has three phases: recruitment, stimulation, and collaboration. This article mainly reports the survey results of 29 participants collected during the teacher recruitment phase. In the recruitment survey, the majority of participants expressed motivation to increase their knowledge regarding marine environmental issues as well as to gather teaching resources. Data collected from the Stages of Concern (SoC) questionnaire revealed that only seven participants considered themselves experienced at teaching marine environmental science. These participants were either concerned about the effect on students of teaching in this field or interested in working with others. Six out of these seven participants continued to be active in the CoP program. Unfortunately, the majority of participants presented nonuser traits, had the highest concerns regarding stage 0 (awareness) or stage 1 (informational), and were less willing to remain in the program. This study endorses the theoretical model of the SoC, finding that the higher level of concern a participant has, the more likely he/she will be to continue to engage in professional development. The results also suggest that CoP as the goal of a professional program may fulfill the demands of experienced users regarding collaboration and improving learning outcomes.